2015
DOI: 10.1177/0020764015614594
|View full text |Cite
|
Sign up to set email alerts
|

Psychiatric disorder and work life: A longitudinal study of intra-generational social mobility

Abstract: Employees suffering from psychiatric disorder do not maintain their social class or remain in the labour force to the same extent as individuals without those problems, irrespective of their parental class. Our results support the social drift hypothesis that individuals with poor psychiatric health move downward in the social hierarchy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 23 publications
0
10
0
Order By: Relevance
“…Chronic diseases such as cancer were expected to be the most likely to create health selection into social mobility and mortality since cancer mortality should be preceded by a period of time in poor health long enough to affect a career. Although suicide may be thought to be preceded by psychiatric disorders that potentially influences social mobility chances [33] as well, previous studies have found little support for selection effects within the labor market [4,9,10,14,17,18]. Psychiatric health selection effects may be more evident in the pathway out of the labor market, particularly for those individuals with very severe psychiatric disorder such as schizophrenia [9,17].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Chronic diseases such as cancer were expected to be the most likely to create health selection into social mobility and mortality since cancer mortality should be preceded by a period of time in poor health long enough to affect a career. Although suicide may be thought to be preceded by psychiatric disorders that potentially influences social mobility chances [33] as well, previous studies have found little support for selection effects within the labor market [4,9,10,14,17,18]. Psychiatric health selection effects may be more evident in the pathway out of the labor market, particularly for those individuals with very severe psychiatric disorder such as schizophrenia [9,17].…”
Section: Discussionmentioning
confidence: 99%
“…But findings are inconclusive on whether this is the case. Much research suggests that social mobility is not associated with previous health [4][5][6][7][8][9][10][11], whereas some findings indicate a modest effect of health on social mobility [12][13][14][15][16][17], on financial deprivation [18] and the attainment of supervisory/managerial positions and income change [19].…”
Section: Introductionmentioning
confidence: 99%
“…Childhood SES, across a wide range of levels, has been associated with disparate outcomes in mental health, cognitive development, and academic achievement (Brooks-Gunn and Duncan 1997;Sirin 2005;Noble et al 2007;Reiss 2013). These associations are thought to arise through diverse causal pathways, including (i) direct SES-linked environmental effects on cognitive outcomes (Ritsher et al 2001;Kendler et al 2015), (ii) the capacity of mental health difficulties or low cognitive performance to negatively impact SES (Tiikkaja et al 2016), and (iii) the existence of factors that simultaneously increase risk for lowered SES and cognitive difficulties (Trzaskowski et al 2014;Hill et al 2016).…”
Section: Introductionmentioning
confidence: 99%
“…The risk of mental disorders in populations, most notably depression, does not occur randomly in developed nations. Rather, the gradient of risk is steeply slanted toward the disadvantaged [155][156][157][158][159]. From the nutritional perspective, childhood adversities (which already increase risk of later-life NCDs) predict subsequent unhealthy dietary choices in adulthood [160].…”
Section: Disadvantage Compoundedmentioning
confidence: 99%